Roller-ski aerobic high-intensity interval training improves the VO2max and anaerobic power in cross-country skiers - Ates, B.; Cetin, E. (International Journal of Applied Exercise Physiology, 2017)
The purpose of this study was to investigate the 8-week of roller-ski aerobic high-intensity interval training on aerobic and anaerobic power in cross-country skiers. 10 male [age, 18,28±2,1 years; height, 171,26±4,12 cm; weight, 61,39±6,28 kg] and 8 female [age, 16,05±0.3 years; height, 158,3±6,47 cm; weight, 49,34±0.7 kg] junior cross-country skiers completed the study. All skiers performed 2x2-km all-out uphill intervals with roller-skis, 3 times a week, in addition to their traditional training program. Measurements included VO2max, anaerobic power, and also for 2-km time-trial performance. All values were listed as pre-to post-test mean [±SD], significant level, and percentage changes [%]. Pre-to post-testing changes in VO2max, anaerobic power, and also 2-km time-trial performance were significantly higher during all post-test trials in all groups [p<0.005]. As a result, we suggest that the skiers should integrate the roller-ski aerobic high-intensity interval uphill models in their training programs for improving performance.